ON ONE COMPLETE AND MINIMAL SET OF BUILT-IN CONSTANTS FOR BACKUS FP SYSTEM - Martirosyan, G.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2012)
In the present paper the completeness and the minimality of the set of the following built-in constants of Backus FP system are proved: Identity, Head, Tail, Append left, Equals, Composition, Constuction, Condition, Constant.